Pathological Fracture of the Proximal Femur in Osteosarcoma: Need for Early Radical Surgery?. (18th March 2012) - Chandrasekar, C. R.; Grimer, R. J.; Carter, S. R.; Tillman, R. M.; Abudu, A.; Jeys, L. M.; Cheung, W. G. H.; Sharma, R.
Abstract : Seventeen patients underwent treatment for a pathological fracture of the proximal femur due to osteosarcoma. Their age range was from 9 to 84 (mean age 42) with nine patients under the age of 40 and eight above the age of 40. Twelve patients had a fracture at diagnosis and five developed a fracture after the diagnosis. Seven patients had metastatic disease at diagnosis. Five patients were referred after internal fixation of the fracture prior to diagnosis. Chemotherapy was used when appropriate and eight patients then underwent limb salvage surgery, six had an amputation, and three had palliative treatment. The estimated five-year survival was 14%. These results are significantly worse than expected, and it proved impossible to identify any group who fared well. The high incidence of metastases both at diagnosis and subsequently suggests this group of patients are at very high risk. Review of multicentre data may suggest an optimum treatment for this patient group.